Epithelial and sensory mechanisms of nasal hyperreactivity. Issue 5 (26th February 2022) - Velasco, Enrique; Delicado‐Miralles, Miguel; Hellings, Peter W.; Gallar, Juana; Van Gerven, Laura; Talavera, Karel
Abstract: "Nasal hyperreactivity" is a key feature in various phenotypes of upper airway diseases, whereby reactions of the nasal epithelium to diverse chemical and physical stimuli are exacerbated. In this review, we illustrate how nasal hyperreactivity can result from at least three types of mechanisms: (1) impaired barrier function, (2) hypersensitivity to external and endogenous stimuli, and (3) potentiation of efferent systems. We describe the known molecular basis of hyperreactivity related to the functional impairment of epithelial cells and somatosensory innervation, and indicate that the thermal, chemical, and mechanical sensors determining hyperreactivity in humans remain to be identified. We delineate research directions that may provide new insights into nasal hyperreactivity associated with rhinitis/rhinosinusitis pathophysiology and therapeutics. The elucidation of the molecular mechanisms underlying nasal hyperreactivity is essential for the treatment of rhinitis according to the precepts of precision medicine.